PENGARUH PENGENCERAN ASAM SULFOSALYSIL TERHADAP PEMERIKSAAN POSITIF PROTEIN URIN - Widyastuti, Rahma (Universitas Muhammadiyah Surabaya)
PENGARUH PENGENCERAN ASAM SULFOSALYSIL TERHADAP PEMERIKSAAN POSITIF PROTEIN URINÂ Rahma W, S.Si, M.Kes.blue4rahma@gmail.com Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractThe examination of urinary protein, there are several kinds of methods that can be used is 20% sulfosalysil acid method, stick, acetate acid, bence jones, and Esbach. Sulfosalysil acid method is a non-specific indicator, the method is sensitive to the protein in a concentration of 0.002%. In the laboratory there are health centers that use sulfosalysil acid reagent for examination of urinary protein, in addition to using a stick of urine (strip dye). Reagent consumption is expected to have economic value, it is necessary dilution reagent. Dilution reagent can reduce the level of Corrosiveness to laboratory personnel, the smaller the concentration of reagent concentrations the less the level of corrosive. So it apost prandialears a formulation of the problem in this research is